Structural Design of a Mixed-Height Islamic Boarding School Building Under Seismic Loading: A Case Study of a Pesantren in Diwek, Jombang Regency - Riky Dwi Prayogo; Titin Sundari; Totok Yulianto; Meriana Wahyu Nugroho (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The structural design of a three-storey pesantren (Islamic boarding school) dormitory facility located in Diwek District, Jombang Regency, is presented in this study. The design was performed in accordance with Indonesian National Standards SNI 2847:2019 (Reinforced Concrete Structural Design), SNI 1726:2019 (Earthquake Load Provisions), and SNI 1727:2020 (Minimum Building Load Requirements). A Special Moment Resisting Frame System (SRPMK), recognized for its enhanced ductility and seismic resilience, was selected as the primary structural system. The structural elements were systematically designed and verified to meet all regulatory requirements. The floor slab was dimensioned at 120 mm thickness, whereas staircase components exhibited riser heights of 170 mm and tread depths of 300 mm. Beam elements of varying capacities were proportioned as follows: primary beam B3 (450 mm × 700 mm), secondary beam BA3 (350 mm × 600 mm), and tertiary beam BA4 (200 mm × 300 mm). Two sizes of grade beam elements were designed, namely S3 (400 mm × 600 mm) and S4 (300 mm × 500 mm). The principal column section was established at 600 mm × 600 mm. The foundation system consisted of a maximum pile cap measuring 1750 mm × 1750 mm with 500 mm thickness, supported by four driven piles of 250 mm × 250 mm cross-section. All structural components demonstrated adequate capacity margins relative to design loads, thereby confirming the structural safety and functionality of the facility.